Analisis Transaksi Jual Beli Online dalam Persefektif Ekonomi Islam: Tinjauan terhadap Kepatuhan Syariah - Fata, Zainol (Journal of Islamic Economics Studies and Practices, 2024)
In the past, buying and selling transactions had to bring together sellers and buyers to meet directly or face to face so that with this meeting there was an exchange or transfer of goods from seller to buyer so that a transaction occurred, but over a long period of time. Nowadays, with the development of technology, face-to-face meetings can no longer be avoided, but nowadays meetings are held online. Both parties do not have to meet in person to carry out buying and selling transactions because E-commerce has made it easy for consumers to make purchases and sales online without geographical restrictions. However, in the context of Islamic economics, it is very important to note that online buying and selling transactions must also pay attention to and comply with sharia principles in their transaction activities. This research use desciptive qualitative approach. This research uses a library research approach that collects data in the form of words and images, not data in the form of numbers. In the research it can be concluded that online buying and selling transactions are the same as buying and selling transactions in general, but the media used is different. So online buying and selling transactions must follow the general terms and conditions of buying and selling